The Costs of Confronting Osteoporosis: Cost Study of an Australian Fracture Liaison Service. (18th April 2018) - Major, Gabor; Ling, Rod; Searles, Andrew; Niddrie, Fiona; Kelly, Ayano; Holliday, Elizabeth; Attia, John; Bogduk, Nikolai
ABSTRACT: Fracture liaison services (FLS) are an accepted approach to lowering rates of osteoporotic refractures. However, resource allocations to FLS are open to challenge, as most relevant cost analyses are based on anticipated, rather than observed, benefits. To support informed decision making, we have estimated the cost of operating an FLS, from the perspective of the Australian health system, with real life costs. On the basis of hospital records, we compared total costs of two cohorts of patients presenting with minimal trauma fractures (MTFs) at two hospital emergency departments (EDs) across a 6‐month period (July to December 2010). The treatment cohort (FLS Cohort, n = 515) attended an ED at a hospital offering FLS post‐fracture care; the Usual Care Cohort ( n = 416) attended an ED at a hospital without an FLS. Hospital records were reviewed for further attendance of both groups at their respective hospitals' EDs with refractures for the subsequent 3 years. Costs were constructed from "bottom up" with a "microcosting" approach. Total costs for both cohorts included any FLS and the costs of refractures. Cohort costs were estimated for every 1000 patients over the 3 observed years. Compared with the Usual Care Cohort, the FLS Cohort had 62 fewer fractures per 1000 patients and 617, 275 lower costs over 3 years. In a sensitivity analysis, where 20% of the Usual Care Cohort received FLS preventative treatment, FLS Cohort costs were lower by 880, 154. As both hospitals consistently process around 2000 patients per year, the estimated annual saving is 1.2 million to 1.8 million (Australian dollars). From the perspective of the Australian public health system, investment in FLS can be a financially effective way of reducing the cost of osteoporotic fracture management. © 2018 The Authors JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.